Choosing Opponents in Prisoners' Dilemma: An Evolutionary Analysis - Peter Engseld; Andreas Bergh (Lund University, School of Economics and Management, Department of Economics, 2005)
We analyze a cooperation game in an evolutionary environment. Agents make noisy observations of opponents' propensity to cooperate, called reputation, and form preferences over opponents based on their reputation. A game takes place when two agents agree to play. Pareto optimal cooperation is evolutionarily stable when reputation perfectly reflects propensity to cooperate. With some reputation noise, there will be at least some cooperation. Individual concern for reputation results in a seemingly altruistic behavior. The degree of cooperation is decreasing in anonymity. If reputation is noisy enough, there is no cooperation in equilibrium.
Keywords: C70; C72; 330; Cooperation; Conditioned Strategies; Prisoners Dilemma; Signaling; Reputation; Altruism; Evolutionary Equilibrium